International spillovers of forward guidance shocks. (7th September 2021) - Jones, Callum; Kulish, Mariano; Rees, Daniel M.
Summary: We estimate a two‐country model of the United States and Canada over the post 2009 sample to study the cross‐country spillovers of forward guidance shocks. To do so, we propose a method to identify forward guidance shocks during the fixed interest rate regime. The estimated forward guidance shocks coincide with significant U.S. monetary policy announcements such as the introduction of calendar‐based guidance in 2011. While a 2‐quarter expansionary forward guidance shock decreases Canadian output by about 0.2% to 0.4% on impact, we find that the United States and Canada were both better off by responding with expansionary monetary policy to the large contractionary shocks that took place during the Great Recession. The central message of our paper is that the focus on whether monetary policy spillovers are expansionary or contractionary is incomplete. What matters is whether the combined monetary policy response is stabilizing in aggregate.